Pengaruh Model Pembelajaran Generatif Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas V Sekolah Dasar - Zutri Parwines; Meria Ultra Gusteti (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
The purpose of this research is to know the effect of learning model Generative on students mathe matical ability. This research was conducted at SD Islam At-Taubah East Jakarta. The research design used is treatment by level 2x2, with independent variable is the learning model that is Generative and conventional (expository), dependent variable is mathematical communication ability. Sampling technique used random sampling. The result of this research is first learning Generative effective to improve student communication ability so that this model can be used by elementary school teacher in building material. Second, the learning model influences students' mathematical communication skills